2023
DOI: 10.3390/microorganisms11020438
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Evolution of Integrative and Conjugative Elements Involved in Bacterial Aromatic Compound Degradation and Their Utility in Environmental Remediation

Abstract: Integrative and conjugative elements (ICEs) are mobile DNA molecules that can be transferred through excision, conjugation, and integration into chromosomes. They contribute to the horizontal transfer of genomic islands across bacterial species. ICEs carrying genes encoding aromatic compound degradation pathways are of interest because of their contribution to environmental remediation. Recent advances in DNA sequencing technology have increased the number of newly discovered ICEs in bacterial genomes and have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Originally discovered on plasmids, the TA system was thought to be responsible for the stability of the plasmid [ 1 ]. Plasmid stabilization is maintained through the action of PSK, which functions to retain plasmids within the cell by killing dividing cells that have lost plasmids [ 12 ]. However, many studies argue this mechanism, with Tim F. Cooper et al concluding that PSK does not contribute to plasmid stability and that the stabilization of plasmids encoding the TA system is achieved through plasmid-plasmid competition [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally discovered on plasmids, the TA system was thought to be responsible for the stability of the plasmid [ 1 ]. Plasmid stabilization is maintained through the action of PSK, which functions to retain plasmids within the cell by killing dividing cells that have lost plasmids [ 12 ]. However, many studies argue this mechanism, with Tim F. Cooper et al concluding that PSK does not contribute to plasmid stability and that the stabilization of plasmids encoding the TA system is achieved through plasmid-plasmid competition [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The modular nature of ICEs has significant implications for the evolution of bacterial diversity and adaptation. ICEs facilitate the horizontal transfer of a multitude of genes between bacteria via conjugation machinery, thereby conferring advantageous traits such as antibiotic resistance, metal resistance, and virulence upon the recipient host [ 11 , 12 ]. The escalating issue of drug resistance, worsened by the existence of ICE, poses a significant threat to human life and health globally.…”
Section: Introductionmentioning
confidence: 99%
“…The integration sites in the genome of the recipient cell, such as the structural genes for tRNAs, have been reported for many conjugative transposons (Wozniak and Waldor, 2010;Delavat et al, 2017). Although ICEs often carry cargo genes involved in pathogenicity, antibiotic resistance and heavy metal resistance to endow hosts with phenotypes beneficial for niche adaptation (Bellanger et al, 2014), they are also known to carry cargo genes for the catabolism of xenobiotic compounds (Hirose, 2023). ICEclc is a well-known ICE in xenobiotic biodegradation and carries cargo genes involved in the metabolism of chlorocatechol (clc genes) and aminophenol.…”
Section: Integrative and Conjugative Elementsmentioning
confidence: 99%
“…This bacterial strain provide insight into the roles of ICEs in the evolution of catabolic pathways for the biodegradation of chlorinated aromatic compounds. On degradative ICEs, catabolic gene products (e.g., bph , nah , and sal ) that are related to the same substrate always share nearly 100% identity, whereas the sequences of the gene products of the transmission module exhibit variations ( Mohapatra et al, 2022 ; Hirose, 2023 ). Although it has been suggested that there is a mechanism governing catabolic gene insertion and exchange on ICEs, there is little evidence to support this idea.…”
Section: Introductionmentioning
confidence: 99%
“…In a 2003 study by Ariane Toussaint et al, the biphenyl catabolic transposon Tn 4371 was thoroughly sequenced and analyzed, revealing its mosaic structure with multiple building blocks, and a new family of genomic island was proposed(8). Although Tn 4371 has never been proven to transfer conjugally, the designation of ICE Tn 4371 family has been used to include a growing number of ICEs (9) (10) (11) (12). Ohtsubo et al compared 112 related elements and showed that βγ-type ICEs (a sub group of Tn 4371 -related ICEs from β and γ-proteobacterial species) have distinct conserved structure and distinguishable from those from α proteobacteria (αI and αII types).…”
Section: Introductionmentioning
confidence: 99%